1993
DOI: 10.1126/science.7690989
|View full text |Cite
|
Sign up to set email alerts
|

A Single Phosphotyrosine Residue of Stat91 Required for Gene Activation by Interferon-γ

Abstract: Interferon-gamma (IFN-gamma) stimulates transcription of specific genes by inducing tyrosine phosphorylation of a 91-kilodalton cytoplasmic protein (termed STAT for signal transducer and activator of transcription). Stat91 was phosphorylated on a single site (Tyr701), and phosphorylation of this site was required for nuclear translocation, DNA binding, and gene activation. Stat84, a differentially spliced product of the same gene that lacks the 38 carboxyl-terminal amino acids of Stat91, did not activate trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
505
0
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 773 publications
(524 citation statements)
references
References 11 publications
12
505
0
7
Order By: Relevance
“…In mammals, naturally occurring Stat1 variant Stat1␤ lacks the last 38 residues in the C-terminal Transcriptional activation domain (TAD) of Stat1(␣) and is believed to derive from the same gene mostly due to an RNA processing (Muller et al, 1993;Schindler et al, 1992). However, the C-terminus of Stat1(␣) is just required for complete activation of IFN␥-dependent transcription but not for type I IFN-dependent transcription (Shuai et al, 1993;Wen et al, 1995), indicating a dispensable role of complete TAD sequence of Stat1(␣) protein in type I IFN response. Crucian carp Stat1 includes a truncated TAD but also contains a conserved tyrosine site Tyr699 (corresponding to Tyr701 in mammalian Stat1s) (Zhang and Gui, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, naturally occurring Stat1 variant Stat1␤ lacks the last 38 residues in the C-terminal Transcriptional activation domain (TAD) of Stat1(␣) and is believed to derive from the same gene mostly due to an RNA processing (Muller et al, 1993;Schindler et al, 1992). However, the C-terminus of Stat1(␣) is just required for complete activation of IFN␥-dependent transcription but not for type I IFN-dependent transcription (Shuai et al, 1993;Wen et al, 1995), indicating a dispensable role of complete TAD sequence of Stat1(␣) protein in type I IFN response. Crucian carp Stat1 includes a truncated TAD but also contains a conserved tyrosine site Tyr699 (corresponding to Tyr701 in mammalian Stat1s) (Zhang and Gui, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Crucian carp Stat1 includes a truncated TAD but also contains a conserved tyrosine site Tyr699 (corresponding to Tyr701 in mammalian Stat1s) (Zhang and Gui, 2004). In mammals, IFN signaling phosphorylates Tyr701 of Stat1 resulting in nuclear translocation, DNA binding, and gene activation (Shuai et al, 1993). A more recent study showed that upon IFN treatment, Atlantic salmon Stat1 is phosphorylated at tyrosine residues and translocated from cytoplasm to nucleus within 1 h (Skjesol et al, 2010), indicating that, similar to mammalian counterparts, fish Stat1 functions as a transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phosphorylation can be catalyzed by Jak family kinases, intrinsic receptor tyrosine kinases and other cellular tyrosine kinases such as c-src. Once tyrosine phosphorylated, STAT proteins form dimers, translocate to the nucleus, and bind to speci®c DNA elements (Chen et al, 1998;Shuai et al, 1993Shuai et al, , 1994. In this elegant manner, STATs modulate the expression of target genes in response to cytokines.…”
Section: Stat Signaling Pathwaymentioning
confidence: 99%
“…The binding of Stats to cytokine receptors brings them to close proximity with the Jak kinases which phosphorylate a single residue at their carboxyl-terminal domain. That event facilitates homo-or hetero-dimerization of the activated Stat proteins and their accumulation in the nucleus where they regulate gene expression [6][7][8][9].…”
Section: Mechanisms Of Cytokine-induced Nuclear Import and Export Of mentioning
confidence: 99%